2014
DOI: 10.1007/s10533-014-0049-0
|View full text |Cite
|
Sign up to set email alerts
|

Origin-specific molecular signatures of dissolved organic matter in the Lena Delta

Abstract: Large Arctic rivers discharge significant amounts of dissolved organic matter (DOM) into the Arctic Ocean. We sampled natural waters of the Lena River, the Buor-Khaya Bay (Laptev Sea), permafrost melt water creeks, ice complex melt water creeks and a lake. The goal of this study was to characterize the molecular DOM composition with respect to different water bodies within the Lena Delta. We aimed at an identification of source-specific DOM molecular markers and their relative contribution to DOM of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 66 publications
5
25
2
Order By: Relevance
“…Both CDOM and DOC were highly correlated, displaying a similar relationship as found for the coastal Canadian Arctic (Walker et al, 2009; see Figure 2), although with a higher a 350 relative to DOC in the Lena delta waters. The presented values are comparable to other studies previously conducted in this region, with a 350 (a 440 ) values of about 15 m −1 (2.9 m −1 ) at low salinity and DOC concentrations ranging from 500-700 to 100 µM at low and high salinity, respectively (Alling et al, 2010;Stedmon et al, 2011;Semiletov et al, 2013;Walker et al, 2013;Heim et al, 2014;Dubinenkov et al, 2015a).…”
Section: Dynamics and Fate Of Dom In The Lena Delta Regionsupporting
confidence: 90%
See 2 more Smart Citations
“…Both CDOM and DOC were highly correlated, displaying a similar relationship as found for the coastal Canadian Arctic (Walker et al, 2009; see Figure 2), although with a higher a 350 relative to DOC in the Lena delta waters. The presented values are comparable to other studies previously conducted in this region, with a 350 (a 440 ) values of about 15 m −1 (2.9 m −1 ) at low salinity and DOC concentrations ranging from 500-700 to 100 µM at low and high salinity, respectively (Alling et al, 2010;Stedmon et al, 2011;Semiletov et al, 2013;Walker et al, 2013;Heim et al, 2014;Dubinenkov et al, 2015a).…”
Section: Dynamics and Fate Of Dom In The Lena Delta Regionsupporting
confidence: 90%
“…Subsequently, with an enhanced input of DOM (especially CDOM) into the Arctic Ocean, changes in the radiant heating in the upper meters of the ocean as well as a possible increase in the sea-ice melt rates might be foreseen (Granskog et al, 2015). Furthermore, the characteristics of DOM have been shown to be a powerful proxy for tracing organic substances with permafrost origin O'Donnell et al, 2014;Dubinenkov et al, 2015a). Moreover, long-term studies concerning the quantification, composition and dynamics of DOM, from fresh to marine waters in the main rivers flowing into the Arctic Ocean, are needed to improve the understanding of DOM dynamics, its role in the carbon cycle pathways.…”
Section: Dynamics and Fate Of Dom In The Lena Delta Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, 5, 6, and 7). These differences in DOM composition between organic mat and permafrost soil layers were consistent with previous observations in arctic (Mann et al, 2012;Cory et al, 2013;Hodgkins et al, 2014;Spencer et al, 2015;Dubinenkov et al, 2015) and subarctic soils (e.g., Kaiser et al, 1997;Cory et al, 2004;D'Andrilli et al, 2010;Tfaily et al, 2013). For instance, Cory et al (2013) used optical proxies to show that organic mat DOM contained higher aromatic C and higher average molecular weight compared to permafrost DOM.…”
Section: Compositional Differences Between Organic Mat and Permafrostsupporting
confidence: 89%
“…Furthermore, multiple studies have suggested that bacterial growth rates and efficiencies are inversely correlated to the average oxidation state of DOM (Meyer, 1994;Vallino et al, 1996;Sun et al, 1997). Given that aromatic C, molecular weight, and oxidation state of DOM have been reported to differ between permafrost and organic mat DOM in arctic soil waters (Hodgkins et al, 2014;Spencer et al, 2015;Dubinenkov et al, 2015), a more detailed view of DOM chemical composition is needed to identify the organic compounds that govern the susceptibility of DOM to aquatic bacterial degradation.…”
Section: Introductionmentioning
confidence: 99%